IMPLEMENTATION OF THE SEMESTER CREDIT SYSTEM PROGRAM IN ISLAMIC EDUCATION LEARNING AT MADRASAH ALIYAH - Habibah, Nur Faiz (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
The implementation of the Semester Credit System (SKS) at Madrasah Aliyah Nurul Qur’an is a strategic step to improve the quality of education and adapt to the demands of modern times. This study aims to provide a detailed description of the planning, implementation, and evaluation of the SKS program at MA Nurul Qur’an Patokan Kraksaan Probolinggo. A qualitative case study approach was used. Data collection techniques included observation, interviews, and documentation, with data analysis based on the Miles and Huberman model through data condensation, data display, and conclusion drawing. The results show that: (1) Planning involved the development of the Medium-Term Work Plan (RKJM) and Annual Work Plan (RKTM), forming a curriculum development team, and drafting SOPs in accordance with central regulations. (2) Implementation followed the established SOPs, used mastery learning, KD-based UKBM, the 2013 curriculum, and mapped students’ learning loads. (3) Evaluation was conducted on the curriculum, program management, and student learning outcomes, considering the program's alignment with the school’s vision and mission. Penerapan Sistem Kredit Semester (SKS) di Madrasah Aliyah Nurul Qur’an merupakan langkah strategis untuk meningkatkan kualitas pendidikan dan menyesuaikan diri dengan tuntutan perkembangan zaman. Penelitian ini bertujuan untuk mendeskripsikan secara mendalam perencanaan, pelaksanaan, dan evaluasi program SKS di MA Nurul Qur’an Patokan Kraksaan Probolinggo. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi, sementara analisis data dilakukan dengan model Miles dan Huberman melalui kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: (1) Perencanaan dilakukan melalui penyusunan RKJM dan RKTM, pembentukan tim pengembang kurikulum, serta penyusunan SOP yang sesuai dengan regulasi pusat. (2) Pelaksanaan program SKS mengikuti SOP, menggunakan pembelajaran tuntas, UKBM berbasis KD, kurikulum 2013, serta pemetaan beban belajar siswa. (3) Evaluasi dilakukan terhadap kurikulum, pengelola, dan hasil belajar siswa, dengan mempertimbangkan kesesuaian program terhadap visi dan misi madrasah.